Suitability Analysis of Tourist Accommodation Locations Towards Landslide Hazard In Malaka Village, North Lombok Regency - Agus Hery Purnomo (International Journal of Geotourism Science and Development, 2023)
Malaka Village is located in the southwest part of North Lombok Regency. The natural beauty of wavy landscape along coastal area has attracted many tourist-accommodation investments took place in this village, although this brings up a dilemma since the potential economic growth in this place faces a complex natural hazard, especially landslides. The purpose of this study is to get an overview of landslide hazard and examine location suitability of tourist accommodation sites in this area, which can later be used as a reference in advocating disaster risk reduction (DRR) measures. The method used in determining landslide hazard index is spatial (GIS) technique that accommodates variables of: slope rise, rock type, land cover, and rainfall. Based on the weighted overlay result, it is concluded that landslides in Malaka can be devastating (dominated by high hazard), which is confirmed by landslide occurrences at the end of 2022 that were very close to the accommodation sites. Also, an occurrence in 2021 has killed a resident in this village. Digital data on tourism-business locations within this area were taken from online platforms and combined with the findings of a geospatial-based landslide analysis. Based on the suitability analysis through an overlay and buffering operation towards accommodation-location and landslide-hazard layer, it is found that 6 of 30 accommodation sites in Malaka are categorized as low suitability accommodation or dominated by a high and very high hazard category. After comparing landslide features on a related literature and characteristics of past landslides in this area, it is suggested that landslides in Malaka are in form of translational-landslide and rockfall type. Collaborative mitigation efforts that are adapted to the landslide hazard problems are urgently needed to prevent high risks in the future.